Hematological toxicity of anti-tumor antibody-drug conjugates: A retrospective pharmacovigilance study using the FDA adverse event reporting system - Mei Rao; Lihua Wu; Hong Chen; Xiaohui Wu; Huiying Wang; Yangyi Chen; Chunmei Chen (PLoS ONE, 2025)
Background Although antibody-drug conjugates (ADCs) have shown significant efficacy in cancer treatment, hematotoxicity remains a serious issue. This study aims to investigate the relationship between ADCs and hematological toxicity. Methods Our study was conducted using data extracted from the U.S. Food and Drug Administration Adverse Events Reporting System (FAERS) from the third quarter of 2011 to the second quarter of 2024. We used four disproportionality analysis methods to measure risk signals. In addition, we analyzed the time-to-onset of hematotoxicity adverse events (AEs). Results A total of 4,803 cases of hematotoxicity AEs associated with ADCs were identified, the median age of patients was 60 years (IQR: 47–72). Different ADCs have different hematotoxicity profiles, among which brentuximab vedotin (BV) and sacituzumab govitecan (SG) were more likely to lead to serious outcomes. The median time-to-onset of hematotoxicity AEs was the shortest for SG at 12 days and the longest for trastuzumab deruxtecan (TG) at 22 days. The hospitalization and mortality rates with hematotoxicity AEs were 30.38% and 18.30%, respectively. Conclusions ADCs are significantly associated with increased reporting of hematotoxicity. A novel hematotoxicity signal that was not disclosed in the drug specifications was observed. The most prominent hematotoxicity AE signals were cytopenia related to inotuzumab ozogamicin (IO), polatuzumab vedotin (PV), loncastuximab tesirine (LT), and tisotumab vedotin (TV); febrile bone marrow aplasia related togemtuzumab ozogamicin (GO), BV, and SG; and myelosuppression related to BV, trastuzumab emtansine (TE), andenfortumab vedotin (EV). Our findings need to be validated by large-scale prospective studies.